Phantom-based radiomics feature test-retest stability analysis on photon-counting detector CT - Hertel, Alexander; Tharmaseelan, Hishan; Rotkopf, Lukas Thomas; Nörenberg, Dominik; Riffel, Philipp; Nikolaou, Konstantin; Weiss, Jakob; Bamberg, Fabian; Schönberg, Stefan; Froelich, Matthias F.; Ayx, Isabelle (European radiology, 2023)
Radiomics image data analysis offers promising approaches in research but has not been implemented in clinical practice yet, partly due to the instability of many parameters. The aim of this study is to evaluate the stability of radiomics analysis on phantom scans with photon-counting detector CT (PCCT).
Online veröffentlicht: 21. Februar 2023
Gesehen am 13.08.2024